Holocene Development and Permafrost History of the Usinsk Mire, Northeast European Russia - Oksanen, Pirita; Kuhry, Peter; Alekseeva, Rimma (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractThis study discusses Holocene vegetation succession, permafrost dynamics and peat accumulation in the Usinsk mire, located in the Pechora lowlands of Northeast European Russia. At present, the area is situated in the extreme northern taiga subzone near the southern limit of permafrost. Reconstructions are based on plant macrofossil analysis, physico-chemical analysis and AMS (accelerator mass spectrometry) radiocarbon dating of two peat profiles investigated in detail. Additional information is available from seven other sites. Organic accumulation started at ca. 11 350 BP (14C yrs). Terrestrialization of ponds was the most common pathway for mire initiation. During a large part of their history, the sites have been Cyperaceae-dominated fens. A change into Sphagnum-dominated ecosystems is recorded at 3700-3000 BP. Permafrost became established around 2300 BP, although first signs of embryonic palsa formation can be tentatively traced back to about 2900 BP. Palsas and peat plateaus have experienced several periods of freezing and entire or partial thawing. The extant permafrost stages are young. The long-term carbon accumulation rate in the investigated sites is 19 g/m2/yr. The average rate of carbon accumulation in the dynamic permafrost stage is 23 g/m2/yr.